Nurse prescribing in Poland: legislative history, trends over time and physicians’ attitudes - Cianciara, Dorota; Wrześniewska-Wal, Iwona; Kobuszewski, Bartosz; Ruiz, Mariusz; Augustynowicz, Anna (Journal of Education, Health and Sport, 2023)
A 2016 a legislative amendment authorized nurses and midwives in Poland to independently prescribe medical drugs and issue prescriptions for the purposes of continuation of treatment previously ordered by a physician. The legislative process was far from perfect, with nurses and midwives voicing their doubts just as well as doctors. Material and methods: Content analysis of documents from the legislative process was conducted, as well as a questionnaire survey among physicians concerning the exercise of these new right in places where doctors work and doctors’ attitudes on the matter. The survey was done in 2017 and 2019, with 547 and 471 physicians participating, respectively. Statistical analysis employed Pearson’s chi-squared test with grouped variables. Results: The main stated reason behind the legalization of nurse and midwife prescribing was the desire to reduce the queues of people waiting for health-care services. Between 2017 and 2019 an insignificant increase in the exercise of these rights occurred, especially in respect of supplementary prescription, i.e. for the purposes of continuation of treatment. The percentage of physicians with a positive attitude to these rights was found to have increased in these years. No variables explicitly linked to a positive attitude were identified. Conclusions: the full, successful and safe use of this opportunity requires continued research into the subject and its conditions, both quantitative and qualitative, as well as appropriate management of the change process on the basis of such data.